MicroglassificationTM: A Novel Technique for Protein Dehydration. Issue 3 (10th January 2014) - Aniket,; Gaul, David A.; Rickard, Deborah L.; Needham, David
<x xml:space="preserve">Abstract</x> The dehydration of biologics is commonly employed to achieve solid‐dose formulation and enhanced stability during long‐term preservation. We have developed a novel process, MicroglassificationTM, which can rapidly and controllably dehydrate protein solutions into solid amorphous microspheres at room temperature. Single bovine serum albumin (BSA) microdroplets were suspended in pentanol or decanol using a micropipette, and the dynamic changes in droplet dissolution were observed in real‐time and correlated to protein's water of hydration, medium's water activity, and microsphere protein concentration. MicroglassificationTM was also carried out at bulk scale, and changes in BSA secondary structure were analyzed by Fourier transform infrared spectroscopy and fluorescence spectroscopy; multimer formation was detected by native gel electrophoresis. BSA concentration in the microsphere increased with solvent exposure time and decreasing water activity. Image analysis at single particle and bulk scale showed the formation of solid BSA microspheres with a maximum protein concentration of 1147 ± 32 mg/mL. The native BSA samples were dehydrated to approximately 450 waters per BSA, which is well below monolayer coverage of 1282 waters per BSA. The secondary structure of MicroglassifiedTM BSA reverted to native‐like conformation upon rehydration with only minor irreversible aggregation (2.7%). Results of the study establish the efficacy of the MicroglassificationTM for the successful dehydration of biologics. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:810–820, 2014